Kekerasan Terhadap Tokoh Perempuan Dalam Cerpen Nusantara Abad 16 Karya Eko Darmoko - Ainiyah, Khurotul; Siska, Risma Ari; Fitriani, Herni (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was motivated by the author's interest in the short story Nusantara Abad 16 by Eko Darmoko which deals with violence against female characters. The method in this research is a qualitative method that produces written data from texts that refer to social problems. The techniques used are data collection, data analysis, and presentation of data analysis results. After conducting research, it can be concluded that there is a form of violence against women in the short story Nusantara Abad 16. Data collection techniques used library, reading and note-taking methods. The library technique is using written sources to obtain data. The problem discussed in this research is how the forms of violence against one of the female characters in the short story Nusantara Abad 16 consist of public violence, namely: sexual violence and non-sexual violence. This research aims to describe forms of violence against women and explain the causes of violence against women in the short story Nusantara Abad 16.